IMPLEMENTASI DAN ANALISIS UNJUK KERJA TEAMSPEAK SEBAGAI ROIP (RADIO OVER IP) PADA KOMUNIKASI TANGGAP BENCANA - Eko Pramono (Informasi Interaktif, 2016)
One of the most reliable models of telecommunication equipment in the event of a disaster is a radio communications device. Radio device with Handy Talky model, has limited communication distance capability. By developing it into RoIP (Radio Over IP), the radio telecommunication system is tied up on VoIP system so that radio telecommunication system becomes more global and able to solve the problem of interoperability in telecommunication problem in general and telecommunication system of disaster response. This study examines the reliability level of RoIP (Radio Over IP) which is implemented in disaster response communication system. Tests include VOX / Switcher, Packet Loss and Delay systems for the use of CODEC and the number of users and the quality of mobile internet from various providers capable of being used for RoIP systems.Keyword:  RoIP, Radio Over IP, VOX, CODEC, disaster response